2007
DOI: 10.1177/0969776407081165
|View full text |Cite
|
Sign up to set email alerts
|

From Disciplining To Dislocation

Abstract: In German cities, area bans (Aufenthaltsverbote) are issued against users of illegalized drugs and other 'undesirables' to bar them from entering certain central city spaces. Drawing on materialist state theory, the expert discourses that legitimize these area bans are analysed in order to understand why this spatial measure of policing is on the agenda right now. I argue that these discourses reveal that area bans are aimed at dislocating undesirables; that they are based on a spatialization of 'danger'; that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 50 publications
(48 reference statements)
0
7
0
3
Order By: Relevance
“…In common with Crawford (2009), Beckett and Herbert (2010) found that the Seattle provisions progressively increased the likelihood of infringement and punishment, but without demonstrable effects upon behaviour. Belina (2007) critiqued the arbitrary and reductive nature of summary police banning powers in Bremen, Germany and observed that the resulting dislocation of 'undesirables' reflected a spatialization of risk that did little to change individual behaviour or assure community safety. In a study of responses to police zonal banning powers in Denmark, Sogaard (2018) found that bans were routinely disregarded, had limited value as a specific deterrent, and fear of being banned exacerbated rather than deterred anti-social behaviours.…”
Section: Deterrence Displacement and Exclusionmentioning
confidence: 99%
“…In common with Crawford (2009), Beckett and Herbert (2010) found that the Seattle provisions progressively increased the likelihood of infringement and punishment, but without demonstrable effects upon behaviour. Belina (2007) critiqued the arbitrary and reductive nature of summary police banning powers in Bremen, Germany and observed that the resulting dislocation of 'undesirables' reflected a spatialization of risk that did little to change individual behaviour or assure community safety. In a study of responses to police zonal banning powers in Denmark, Sogaard (2018) found that bans were routinely disregarded, had limited value as a specific deterrent, and fear of being banned exacerbated rather than deterred anti-social behaviours.…”
Section: Deterrence Displacement and Exclusionmentioning
confidence: 99%
“…The banishment of undesirables from certain urban zones is not restricted to the USA. Belina (2007) documents the introduction of area bans [Aufenthaltsverbote] into the police law of Germany's regions, giving the authorities considerable powers to ban, from a designated zone, anyone reasonably assumed likely to commit a crime. His research in Bremen explores the use of this power to curb the open-air drug scene in the city's principal leisure district, highlighting the way in which the discourse surrounding such bans 'links the mere presence of undesirables to 'crime', making their eviction a task for the police' (Belina 2007: 324).…”
Section: Zoning Out the Problematicmentioning
confidence: 99%
“…The municipally-controlled street system that once acted as an effective monopoly of the public realm in many cities today is being paralleled by the growth of a set of privatized street spaces – including but not limited to shopping malls, privatized railway stations and privatized streets and squares, as well as BIDs. The abandonment of the principle of free, open and democratic access to public space (on the hollowness of such claims, see Eick and Briken, 2011) in favour of a policy of actively excluding (and/or incarcerating) those deemed not to belong is key to the logic of these spaces (Belina, 2007; Eick, 2008).…”
Section: Understanding Security Semi-statesmentioning
confidence: 99%